MANAGEMENT OF FINANCIAL AND ECONOMIC BUSINESS PROCESSES IN ORGANIZATION: MICROLOGISTIC APPROACH - Dmitry V. Olyanich; Olga V. Olyanich (Advanced Engineering Research, 2011)
Questions on the applicability of the methodological background and toolkit of the general management and general logistics for management of the specific area of financial and economic business processes are considered.